KELAS KATA BAHASA SIGULAI KABUPATEN SIMEULUE PROVINSI ACEH - Yulsafli, Yulsafli; Ferdianto (Kodepena Indonesia, 2020)
The purpose of this study was to describe the class of words contained in the Sigulai language, Simeulue Regency, Aceh Province. This research method uses qualitative methods. This research is an attempt to understand the word class in Sigulai language, Simeulue Regency by using a descriptive model. The data analysis technique used a descriptive research model by analyzing word classes from the Sigulai language, and concluding the results of the analysis of word classes in the Sigulai language, Simeulue Regency. The results of this study are that there are 10 word classes in the Sigulai language, Simeulue Regency, Province, namely (1) nouns (nouns), (2) verbs (verbs), (3), adjectives (adjectives) (4), words pronouns (5), adverbs (6), numerals (7), conjunctions, (8) articles, (9) exclamations (interjections), (10) preposition (perposition). suggestions from this research are expected to be able to explaining word classes in the Sigulai language, Simeulue Regency, Aceh Province